How hydrology determines seasonal and interannual variations in water table depth, surface energy exchange, and water stress in a tropical peatland: Modeling versus measurements. Issue 11 (5th November 2015) - Mezbahuddin, M.; Grant, R. F.; Hirano, T.
Abstract: Soil carbon stocks in tropical peatlands have declined recently from water table depth (WTD) drawdown caused by increased frequency and intensity of climate extremes like El Niño and by artificial drainage. Restoration of these carbon stocks under these climatic and anthropogenic disturbances requires improved predictive capacity for hydrological feedbacks to ecological processes. Process‐based modeling of tropical peatland ecohydrology could provide us with such capacity, but such modeling has thus far been limited. We aimed at using basic processes for water and O2 transport and their effects on ecosystem water, carbon, and nitrogen cycling to model seasonal and interannual variations of WTD and surface energy exchange. We tested these processes in a process‐based model ecosys in a drained tropical Indonesian peatland from an El Niño year 2002 to a wetter year 2005. WTD was modeled from hydraulically driven water transfers controlled vertically by precipitation versus evapotranspiration (ET) and laterally by discharge versus recharge to or from an external reference WTD. These transfers caused WTD drawdown and soil drying to be modeled during dry seasons, which reduced ET and increased Bowen ratio by lowering stomatal conductance. More pronounced dry seasons in drier years 2002–2004 versus wetter year 2005 caused deeper WTD, more intense peat drying, and greater plant water stress. These modeled trends were well corroborated by site measurements as apparent in regression statistics of modeled versus observed WTD ( R 2  > 0.8), latent heat ( R 2  > 0.8), and sensible heat ( R 2  > 0.7) fluxes. Insights gained from this modeling would aid in predicting the fate of tropical peatlands under future drier climates. Key Points: Ecosys modeled tropical peatland WTD by a vertical‐lateral hydraulic scheme Deeper WTD caused peat drying and reduced stomatal conductance in dry seasons Stomatal limitation to transpiration was stronger in drier dry seasons